Pengaruh Pengetahuan Akuntansi, Pengalaman Usaha dan Skala Usaha Terhadap Proses Pengambilan Keputusan pada UMKM di Labuhanbatu - Suci Nurindah Sari; Mulya Rafika; Mulkan Ritonga (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to analyze the influence of accounting knowledge, business experience, and business scale on the decision-making process of Micro, Small, and Medium Enterprises (MSMEs) in Labuhanbatu Regency. The population in this study was 96 MSMEs in the trade sector. The study used primary data obtained through questionnaires distributed to business owners. The analytical method used was multiple linear regression analysis with the assistance of SPSS software. The results indicate that accounting knowledge has a significant influence on MSME decision-making, as an understanding of accounting helps business owners evaluate their financial condition and determine strategic steps. Meanwhile, business experience did not have a significant effect on decision-making. On the other hand, business scale was shown to have a significant influence on decision-making, as the larger the business scale, the more complex the decisions that must be made. This research is expected to provide considerations for improving the quality of MSME management.